1985
DOI: 10.2166/nh.1985.0009
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Analysis of Low Flows

Abstract: The transformations (i) SMEMAX (ii) Modified SMEMAX (iii) Power and Probability Distributions (iv) Weibull (a,P,y) or Extreme value type 111 (v) Weibull (a,P,O) (vi) Log Pearson Type 111 (vii) Log Boughton are considered for the low flow analysis. Also, different parameter estimating procedures are considered. Both the Weibull and log Pearson can have positive lower bounds and thus their use in fitting low flow probabilities may not be physically justifiable. A new derivation generalizing the SMEMAX transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Based on the literature review, Gumbel has proposed that the third asymptotic distribution of the extreme (smallest) value is one of the most accepted theoretical probability distribution functions for a low flow study (Gumbel, 1958). Later, many scientists suggested that other distributions, such as the generalized extreme value type III (GEV3), the lognormal, and Pearson distributions (Matalas, 1963; Loganathan, 1985; Tasker, 1987), are also acceptable. The parameters of these distributions, however, should be estimated from several statistical methods.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the literature review, Gumbel has proposed that the third asymptotic distribution of the extreme (smallest) value is one of the most accepted theoretical probability distribution functions for a low flow study (Gumbel, 1958). Later, many scientists suggested that other distributions, such as the generalized extreme value type III (GEV3), the lognormal, and Pearson distributions (Matalas, 1963; Loganathan, 1985; Tasker, 1987), are also acceptable. The parameters of these distributions, however, should be estimated from several statistical methods.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have been devoted to the probability distributions most suitable for fi tting the sequences of annual minimum fl ows in different regions and for minima of different averaging intervals, as well as evaluating methods by which to estimate distribution parameters (Matalas 1963;Jozeph 1970;Prakash 1981;Beran and Rodier 1985;Loganathan et al 1985;McMahon and Mein 1986;Singh 1987;Waylen and Woo 1987;Khan and Mawdsley 1988;Sefe 1988;Leppajarvi 1989;Polarski 1989;FREND 1989;Nathan and McMahon 1990b;Russell 1992;Loaiciga et al 1992;Durrans 1996;Lawal and Watt 1996a;Lawal and Watt 1996b;Bulu andOnoz 1997, Jakubowski 2005). The author's task was not to investigate the real distribution of examined series but only to adjust one of the functions applied most frequently to ensure fulfi lment of the Kołmo-gorov λ test condition of conformability.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the minimum annual discharges were fitted using the threeparameter Weibull (WEI3) distribution (or extreme value type III). This distribution was chosen because it is theoretically the parent model of extreme low flows (Gumbel 1954), and hence it was one of the main models considered by Matalas (1963) and Loganathan et al (1985), among others, as suitable for low-streamflow analysis. The WEI3 cumulative distribution function (cdf) is of the form…”
Section: Annual Minimum Flow (Amf) Approachmentioning
confidence: 99%
“…The WEI2 distribution was chosen because its three-parameter counterpart, WEI3, has been widely applied for studying low flows (Matalas 1963). It was also noted that the WEI2 distribution has been used in peak over threshold (POT) flood frequency modeling in the past (Miquel 1984; Groupe de recherche en hydrologie statistique (GREHYS 1996) and in the frequency analysis of low flows (Loganathan et al 1985). Moreover, the generalized Pareto distribution was chosen because it has been widely suggested for exceedance distribution (Davison and Smith 1990;Wang 1991;Madsen et al 1997).…”
Section: Deficit Below Threshold (Dbt) Approachmentioning
confidence: 99%